Receptor-Interacting Protein Kinases 1 and 3, and Mixed Lineage Kinase Domain-Like Protein Are Activated by Sublytic Complement and Participate in Complement-Dependent Cytotoxicity - Lusthaus, Michal; Mazkereth, Niv; Donin, Natalie; Fishelson, Zvi (Frontiers in Immunology, 2018)
The complement system participates in the pathogenesis of many diseases. Complement activation produces several active protein complexes and peptides, including the terminal C5b-9 complexes. It was reported that C5b-9 complexes insert into the plasma membrane and cause membrane perturbation, intracellular calcium surge, metabolic depletion, and osmotic lysis. Previously, we showed that complement-dependent cytotoxicity (CDC) is regulated by JNK and Bid. Here, we demonstrate that three mediators in TNFα-induced necroptosis (regulated necrosis), the receptor-interacting protein kinases, RIPK1 and RIPK3, and mixed-lineage kinase domain-like protein (MLKL), are activated by complement and contribute to CDC. Cell treatment with necrostatin-1, a RIPK1 inhibitor, GSK'872, a RIPK3 inhibitor, or necrosulfonamide and GW806742X, MLKL inhibitors, restrain CDC. These findings were confirmed by using specific siRNAs targeting the synthesis of these proteins. Mouse fibroblasts lacking RIPK3 or MLKL were found to be less sensitive to C5b-9 than were wild-type fibroblasts. Enhanced CDC was achieved by RIPK1 or RIPK3 overexpression but not by the overexpression of a RHIM-RIPK1 mutant nor by a kinase-dead RIPK3 mutant. Necrostatin-1 reduces the CDC of wild-type but not of RIPK3-knockout fibroblasts. Cells treated with a sublytic dose of complement exhibit co-localization of RIPK3 with RIPK1 in the cytoplasm and co-localization of RIPK3 and MLKL with C5b-9 at the plasma membrane. Data supporting cooperation among the RIP kinases, MLKL, JNK, and Bid in CDC are presented. These results provide a deeper insight into the cell death process activated by complement and identify potential points of cross-talk between complement and other inducers of inflammation and regulated necrosis.